Developing contextual teaching and learning-based worksheets to improve fifth grade students' critical thinking (Asian Journal of Educational Technology, 2022)
The purpose of this study was to develop valid, practical, and effective context-based (CTL) worksheets for elementary school students in the fifth grade. We used the Borg and Gall's model for research and development. This study was conducted in an urban elementary school in Bandar Lampung city in Indonesia among teachers and fifth grade students. To collect data, we used a variety of research instruments, including tests and questionnaires. We also used expert judgment for validation. Both qualitative and quantitative analyses were performed on the collected data. Based on the results of expert validation and responses to the questionnaire distributed to the research participants, the findings suggest that the CTL-based worksheets we developed in this study were valid and practical with a significance value of <0.05 obtained from the N-Gain test and paired sample t-test. This implies that the CTL-based teaching materials were effective in improving the critical thinking skills of fifth-grade elementary school students.